Analisa Penerapan Kinerja Frame Relay Pada Pemodelan Jaringan - Putra, Agam Murtio; Sari, Linna Oktaviana (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
The development of the internet today has given us so many benefits for the user as well as for industries that use it as a communication medium that is cheap, effective, and efficient. With the development of Internet and various technologies that go with it then it is also directly proportional to the need for the use of the internet is more reliable and reasonable. In the use ofthe internet there are several technologies that can be used, one of which is Frame Relay. Frame Relay network is a network share (shared services) by utilizing the Permanent Virtual Circuit(PVC) so as to ensure minimum access level CIR (Committed Information Rate) specific. Frame Relay is designed to reduce the processing on each node by reducing the format and proceduresused. In this research, frame relay network modeling and analysis of network performance using software GNS3, frame relay network performance will be determined by the parameters of delay,throughput and packet loss. With this study will be obtained performance of some frame relay network model that can be used as a reference in designing the new network.Keywords: network, frame relay, gns3